Transplantation Tolerance Induced in Humans at the Fetal or the Neonatal Stage - Jean-Louis Touraine; Kamel Sanhadji (Journal of Transplantation)
Patients transplanted with HLA-mismatched stem cells from fetal livers develop transplantation tolerance to donor antigens. Engraftment needs no conditioning regimen prior to transplantation in neonates with severe combined immunodeficiency disease or in human fetal patients having not yet developed any immune maturity, especially T-cell differentiation. The chimeric patients have donor-derived T lymphocytes which progressively demonstrate positive interactions with other host cells. They also can be shown to be tolerant toward both host and donor antigens. The latter tolerance relies upon clonal deletion from the T-cell repertoire, and it results from the contact between thymocytes of donor origin and dendritic cells or macrophages also deriving from donor stem cells. The former tolerance does not imply clonal deletion of T-cells with host reactivity. Numerous T-cells recognizing the allogeneic, host-type antigens are identified in these patients, but these cells are anergized, following interaction with epithelial cells of the host thymus. Induction of transplantation tolerance at the fetal stage requires minimal engraftment only; in the future it will be possible to further amplify the clinical benefit, using additional cell transplants after birth.